Not white enough, not black enough: racial identity in the South African coloured community - Adhikari, Mohamed (Ohio University research in international studies / Africa series)
Continuity and context : an overview of coloured identity in white supremacist South Africa -- History from the margins : changing perceptions of its past within the coloured community -- The predicament of marginality : case studies from the earlier period of white rule -- The hegemony of race : coloured identity within the radical movement during the mid-twentieth century -- The emperor's new clothes : coloured rejectionism during the latter phases of the apartheid era -- New responses to old dilemmas : coloured identity in a transforming South Africa.